Cognitive strategies and level of understanding of academic texts in university entering students - Perú - Mamani-Apaza, William (2021)
The purpose of contemporary university education is to strengthen the capacities of understanding academic texts of future professionals as autonomous agents who manage their learning. Within this framework, the article aimed to determine the degree of relationship between cognitive strategies and the compression of academic texts in Peruvian university students, in order to have a cognitive profile of those entering the university. The study population consisted of 172 first cycle students. The methodology used was descriptive - correlational cross-sectional. It was concluded, due to the correlation coefficient of Spearman's Rho equal to 0.7929 and the estimated P-value of 0.001 lower than the significance level (0.05), that there is a high positive correlation between cognitive strategies and comprehension of the students' academic texts, although this relationship is not decisive.